A systematic review of student learning outcomes in CLIL in LOTE - Pittas, Evdokia; Tompkins, Leah (Frontiers in Education, 2024)
This paper aims to provide a first systematic research overview of student learning outcomes in programs teaching school subjects through languages other than English (LOTE) which are not the mother tongue of the students, according to school- or researcher-administered assessments and stakeholder perspectives, following the PRISMA statement. For brevity, we shall refer to these types of programs as CLIL in LOTE, though we have also included programs which use other labels, such as bilingual education or immersion, due to their similarities with those labeled “content and language integrated learning” (CLIL). The selected studies, published between November 1994 and December 2023, were identified through the search of SCOPUS and EBSCO. In determining which studies to include in the review, we employed the following selection criteria: (1) articles focusing on children and youth (ages 5–17 years), (2) articles focusing on CLIL programs in LOTE, (3) articles focusing on student achievement, (4) articles focusing on studies that have collected primary data, and (5) studies that used school-/researcher-administered assessments (objective) or self/hetero-reported measures (subjective). The screening of titles, abstracts and keywords left a final sample of n = 29 scientific papers, which were then read exhaustively and assessed for methodological quality. Most studies (26 of 29) addressed academic and/or linguistic outcomes, with some studies additionally addressing social/cultural outcomes, behavioral/affective outcomes, and/or (meta)cognitive outcomes. Of the learning outcomes reported, 25 (53%) were positive, five (11%) were negative, four (9%) were neutral, eight (17%) were mixed and four (9%) identified factors influencing outcomes. Theoretically, the study contributes to establishing more general theories about the specific role of CLIL in LOTE in students’ learning. Empirically, the study outlines pathways for future research on CLIL in LOTE. In practice, the study presents challenges identified by stakeholders to suggest pathways forward in CLIL teaching/learning.